CONSORT Harms 2022 statement, explanation, and elaboration: updated guideline for the reporting of harms in randomised trials. (24th April 2023) - Junqueira, Daniela R; Zorzela, Liliane; Golder, Susan; Loke, Yoon; Gagnier, Joel J; Julious, Steven A; Li, Tianjing; Mayo-Wilson, Evan; Pham, Ba; Phillips, Rachel; Santaguida, Pasqualina; Scherer, Roberta W; et al.
Abstract : Randomised controlled trials remain the reference standard for healthcare research on effects of interventions, and the need to report both benefits and harms is essential. The Consolidated Standards of Reporting Trials (the main CONSORT) statement includes one item on reporting harms (ie, all important harms or unintended effects in each group). In 2004, the CONSORT group developed the CONSORT Harms extension; however, it has not been consistently applied and needs to be updated. Here, we describe CONSORT Harms 2022, which replaces the CONSORT Harms 2004 checklist, and shows how CONSORT Harms 2022 items could be incorporated into the main CONSORT checklist. Thirteen items from the main CONSORT were modified to improve harms reporting. Three new items were added. In this article, we describe CONSORT Harms 2022 and how it was integrated into the main CONSORT checklist, and elaborate on each item relevant to complete reporting of harms in randomised controlled trials. Until future work from the CONSORT group produces an updated checklist, authors, journal reviewers, and editors of randomised controlled trials should use the integrated checklist presented in this paper.